Metode Pembelajaran Guru Fiqih dalam Meningkatkan Pemahaman Sholat: Telaah Kitab Mabadi Al-fiqhiyah di MI Taswirotul Ulum Sumbergayam Kepung Kediri - Khoirul Huda, Yusuf (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2024)
Mabadi' Fiqh is a book that is mostly taught in Salafiyyah Islamic boarding schools for beginners. MI Taswirotul Ulum is an institution within the Misbahul Ulum Islamic Boarding School which teaches fiqh using the book Mabadi' al-Fiqihiyah. Students who are still beginners do not have any prior knowledge of Arabic, of course, they will experience difficulties in understanding the book, for this reason, a fiqh teacher is needed to apply effective and efficient learning methods. Based on research conducted by researchers, there are three research findings: (1) The Fiqh learning system that is applied to students at MI Taswirotul Ulum as one of the processes of making students learn to understand Islamic laws is very in line with the character of students at the madrasa and can provide value. spiritual. (2) The method used in the Mabadi al-fiqhiyah book in presenting fiqh material to students at MI Taswirotul Ulum is by using habituation, example, reward, punishment, lecture, question and answer, discussion, sorogan, bandongan, mudzakaroh, stories, assignments, field trips, experiments, drills/exercises, sociodrama, simulations, fieldwork, demonstrations, and group work. (3) There is a positive and significant influence of studying the book Mabadi al-Fiqhiyah on increasing understanding of prayer material by a 0.05. Thus, it can be concluded that to increase students' understanding of prayer, it must be supported by fiqh teacher learning methods in the form of visual, auditory and kinesthetic, so that students' understanding can increase significantly.